Ideologisasi Tafsir Lokal Berbahasa Sunda: Kepentingan Islam-Modernis dalam Tafsir Nurul-Bajan dan Ayat Suci Lenyepaneun - Jajang A Rohmana (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
This article studies the ideological motive of modernist Islam in the indegenous tafsir using local Sundanese language: Nurul-Bajan of Muhammad Romli and Ayat Suci Lenyepaneun of Moh. E. Hasim. Using critical discourse analysis approach, the author shows how the modernist ideology of Islam took place and influenced the interpretation of religious texts (tafsi@r), such as the Sundanese tafsir. This ideological tendency can be understood not only as the life background of the author as a local activist modernist Muslim, but also influenced by the historical situation in the 1970s and 1990s, when the strengthening of ideological rivalry between modernist and traditional Islam. Being Sundanese Muslim living in Sundanese region, they use local language media in the interpretation of the Qur’a>n as an effective tool to diseminate modernist Islam.